Representing mental illness in late medieval France : machines, madness, metaphor - Singer, Julie, 1978- (Gallica (Woodbridge (Suffolk, England)) ;, 2018)
An exploration of the medieval mind as a machine, and how it might be affected and immobiled, in textual reactions to the madness of Charles VI of France.